Stereoselective synthesis of the C33-C44 fragment of palau'amide - Mohapatra, Debendra K.; Nayak, Sabita (Tetrahedron Letters, 2008)
An efficient stereoselective synthesis of the C33-C44 fragment of palau'amide is described using a Sharpless asymmetric epoxidation, a regioselective nucleophilic ring opening of the epoxide, a Grignard reaction and a Luche stereoselective reduction of a keto compound as the key steps. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Cytotoxic; Luche's stereoselective reduction; palau'amide; Sharpless asymmetric epoxidation; Stereoselective